The effect of antigen dose on T cell-targeting vaccine outcome - Rolf Billeskov; Babak Beikzadeh; Jay A. Berzofsky (Human Vaccines & Immunotherapeutics, 2019)
During the past 3–4 decades, an increasing amount of evidence has pointed to the complex role of the antigen dose or T cell receptor (TCR) stimulation strength on the subsequent type, duration and “flavor” or quality of the response. Antigen dose was initially shown to impact Th1/Th2 bias, and later also shown to differentially affect development and induction of Tregs, Th17, T-follicular helper (Tfh), cells, and others. In recent years the quality of both CD4/8 T cells during infections, cancer and/or autoimmunity has turned out to be critical for subsequent disease outcome. Importantly, different vaccination strategies also lead to different types of T cell responses, and the role of the antigen dose is emerging as an important factor as well as a tool for investigators to utilize in fine-tuning vaccine efficacy. This commentary will highlight essential background of how antigen dose can impact and affect the quality of T cell responses, and discuss how this translates in different vaccine settings.